2012
DOI: 10.1002/dev.21011
|View full text |Cite
|
Sign up to set email alerts
|

The unconditioned stimulus pre‐exposure effect in preweanling rats in taste aversion learning: Role of the training context and injection cues

Abstract: The unconditioned stimulus pre‐exposure effect (US‐PE) refers to the interference paradigm in which acquisition of the conditioned response is retarded due to prior experience with the US. Most studies analyzing the psychological mechanisms underlying this effect have been conducted with adult rats. The most widely accepted hypothesis explains this effect as a contextual blocking effect. Contextual cues associated with the US block the conditioned stimulus (CS)‐US association during conditioning. The modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The one-way between-factor analysis did not demonstrate that the Almond and Saccharin groups acquired aversion after the conditioning trials (C1 and C2). With similar parameters, we have found strong evidence of aversion in previous studies (e.g., Arias et al, 2010;Revillo, Arias, & Spear, 2012), but in FIGURE 1 a: Intake data from Experiment 1a. Scores represent the mean saccharin consumption as a function of Group (Water, Almond, or Saccharin), and Day [Conditioning Days 1 and 2 (C1, C2), Extinction days 1 and 2 (E1, E2), and Reacquisition (R) and Testing days].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The one-way between-factor analysis did not demonstrate that the Almond and Saccharin groups acquired aversion after the conditioning trials (C1 and C2). With similar parameters, we have found strong evidence of aversion in previous studies (e.g., Arias et al, 2010;Revillo, Arias, & Spear, 2012), but in FIGURE 1 a: Intake data from Experiment 1a. Scores represent the mean saccharin consumption as a function of Group (Water, Almond, or Saccharin), and Day [Conditioning Days 1 and 2 (C1, C2), Extinction days 1 and 2 (E1, E2), and Reacquisition (R) and Testing days].…”
Section: Discussionsupporting
confidence: 80%
“…It is important to notice that in this study contextual conditioning in the infant rat was observed using a paradigm that is highly dependent on the hippocampus, at least in adult and weaning rats (the context preexposure facilitation effect; Schiffino et al, 2011). These data also suggest the need for a more detailed analysis of the possible role of the hippocampus in the modulation of extinction and other interference paradigms, such as the unconditioned stimulus preexposure effect (Castello, Bobbio, Orellana, & Arias, 2011;Revillo et al, 2012), or latent inhibition (Yap & Richardson, 2005), which seem also to be contextindependent in preweanling rats. As mentioned above, renewal in adult rats (in taste aversion learning or in fear conditioning) is also hippocampus-dependent (Fujiwara et al, 2012;Ji & Maren, 2005), and we did observe renewal after extinction of a conditioned taste aversion.…”
Section: Discussionmentioning
confidence: 85%
“…Both age and strain influenced the amount of NaCl solution consumed at Trial 1. Differences in exposure to the US can affect subsequent associations (Revillo et al 2012). As we were comparing multiple strains at two different ages, we thought it best to control for initial exposure to the US by transforming the data to a percent change from Trial 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not so clear during infancy. For example, in this ontogenetic stage, a context change was not found to attenuate the magnitude of some interference effects, such as the US‐preexposure effect (Revillo, Arias, & Spear, ), extinction (Yap & Richardson, ), and latent inhibition (Yap & Richardson, ). These results are consistent with studies that failed to find long‐term retention of contextual conditioning in infant rats under 21 days of age (Murawski & Stanton, ; Rudy & Morledge, ; Schiffino, Murawski, Rosen, & Stanton, ).…”
Section: Introductionmentioning
confidence: 92%